Smart Cities and Product-Service Systems-A Conceptual Framework for Urban Sustainability - Paalosmaa, Tomi (John Wiley & Sons, 2025)
This conceptual paper delves into the validity of product-service systems (PSS) in driving smart city development. Existing research often treats smart cities as primarily technology-driven constructs, overlooking how organisational measures and strategies such as PSS can contribute to their sustainability ambitions and, thus, smart city initiatives. Through an integrative literature review of selected 145 academic papers across smart cities, sustainability, innovation, digitalisation and product-service systems, this paper introduces a framework that maps PSS onto six core dimensions of the Smart City concept—dimensions identified from the previous research, never before presented together. The findings reveal that PSS enables organisations to transcend beyond isolated organisation focused sustainability driven solutions into wider smart urban surroundings and capabilities. The framework emphasises how PSS can contribute to environmental goals, governance reforms, social inclusion, and economic resilience, thus, being able to provide value for both private and public actors, and citizens. The paper addresses a key research gap and calls for empirical validation to further study how PSS can contribute as a scalable and designable enabler of smart city development.
Keywords: city design; governance; planning & policy; smart cities; smart cities applications; fi=Tuotantotalous tekn|en=Industrial Management tech|